2014
DOI: 10.1021/sb500020g
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Pyruvate Decarboxylase and Alcohol Dehydrogenase Increases Ethanol Production in Escherichia coli

Abstract: Ethanol is an important biofuel. Heterologous expression of Zymomonas mobilis pyruvate decarboxylase (Pdc) and alcohol dehydrogenase (AdhB) increases ethanol production in Escherichia coli. A fusion of PDC and ADH was generated and expressed in E. coli. The fusion enzyme was demonstrated to possess both activities. AdhB activity was significantly lower when fused to PDC than when the two enzymes were expressed separately. However, cells expressing the fusion protein generated ethanol more rapidly and to higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Fusion proteins can lead to increased effectiveness due to substrate channelling even if the measured activities of the two individual partners decreases. This was reported earlier from our lab [49] as well as is shown in this study. Presently assays to measure quantitative cellulose degradation in vivo are not available.…”
Section: Discussionsupporting
confidence: 92%
“…Fusion proteins can lead to increased effectiveness due to substrate channelling even if the measured activities of the two individual partners decreases. This was reported earlier from our lab [49] as well as is shown in this study. Presently assays to measure quantitative cellulose degradation in vivo are not available.…”
Section: Discussionsupporting
confidence: 92%
“…Previously we and others have shown that individual shell proteins, which form the hexameric tiles of the BMC casing, generate long filamentous macromolecular structures when overproduced in the host bacterial cells 30,38 . These structures are particularly apparent with…”
Section: Discussionmentioning
confidence: 99%
“…Genes from Z. mobilis contribute to the standard biology of the International Genetically Engineered Machine registry, especially with unique characteristics such as pdc (ZMO1360, EC: 4.1.1.1), adhB (ZMO1596, EC:1.1.1.1), extracellular sucrase gene sacC (ZMO0375, EC:3.2.1.26), and glf (ZMO0366, glucose facilitated diffusion protein). For example, the ethanol production module of the fusion enzymes, Pdc and AdhB from Z. mobilis (Part:BBa_K1122673), could increase ethanol yields and productivity in E. coli and lactic acid bacteria (Nichols et al ., ; Chen et al ., ; Flynn et al ., ; Lewicka et al ., ).…”
Section: Classical Genetics Tools and Emerging Technologymentioning
confidence: 97%